Analiza wskaźnika optymizmu analityków - wprowadzenie - Porcenaluk, Paweł (The analysis of the analysts' sentiment index – introduction, 2006)
WOA - the sentiment index is a tool supporting investment process. This kind of index should be a powerful tool to increase the value of our portfolio. The conclusion from the analysis is that WOA index effectiveness is small. Similar results are observed on other financial markets. The main problem is that recommendations are biased and influenced by some psychological elements like hope and fear. It means that we can observe more positive recommendations on growing market (which are higher than present market value) and more negative recommendations (which are lower than present market value) when the market value falls. In general more than 50% of the recommendations generate loss.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 401-408